2020
DOI: 10.1097/ico.0000000000002353
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Laser In Situ Keratomileusis Flaps Created Using Single-Functional Versus Multifunctional Femtosecond Laser for Refractive Surgery

Abstract: Purpose: To compare laser in situ keratomileusis flaps created at the programmed target thickness of 120 μm using the LenSx multifunctional and the FS200 single-functional femtosecond lasers as evaluated by anterior segment optical coherence tomography (AS-OCT). Methods: This was a prospective, comparative, consecutive, blinded, nonrandomized study. Patients with stable refraction for over a year were consecutively allocated to the LenSx group or the FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similar results with excellent agreement of intended and measured cap thickness are shown by Reinstein et al 19 and Zhao et al 20 using the Visumax laser platform (Carl Zeiss Meditec) or for LASIK flaps with a deviation of less than 10 µm in eye bank corneas, 15 but some of those studies show a similar deviation but with a lower SD than in our data. A study by Colombo-Barboza was able to show a higher deviation from the intended measures for LASIK flaps but was significant at only 2 of 20 points measured, 21 and Parafita-Fernandez et al 22 had significantly thicker flaps than intended. Alio Del Barrio et al 23 found a thicker cap than expected created by the Visumax laser platform (Carl Zeiss Meditec), in contrast to fs flaps that were closer to the target thickness in the same trial, but Ozgurhan et al 24 reported that they did not find a significant deviation from intended cap thickness for either SMILE or fs-LASIK.…”
Section: Discussionmentioning
confidence: 88%
“…Similar results with excellent agreement of intended and measured cap thickness are shown by Reinstein et al 19 and Zhao et al 20 using the Visumax laser platform (Carl Zeiss Meditec) or for LASIK flaps with a deviation of less than 10 µm in eye bank corneas, 15 but some of those studies show a similar deviation but with a lower SD than in our data. A study by Colombo-Barboza was able to show a higher deviation from the intended measures for LASIK flaps but was significant at only 2 of 20 points measured, 21 and Parafita-Fernandez et al 22 had significantly thicker flaps than intended. Alio Del Barrio et al 23 found a thicker cap than expected created by the Visumax laser platform (Carl Zeiss Meditec), in contrast to fs flaps that were closer to the target thickness in the same trial, but Ozgurhan et al 24 reported that they did not find a significant deviation from intended cap thickness for either SMILE or fs-LASIK.…”
Section: Discussionmentioning
confidence: 88%